Amorphous carbon-encapsulated Si nanoparticles loading on MCMB with sandwich structure for lithium ion batteries. (20th May 2019) - Fan, Peng; Mu, Tiansheng; Lou, Shuaifeng; Cheng, Xinqun; Gao, Yunzhi; Du, Chunyu; Zuo, Pengjian; Ma, Yulin; Yin, Geping
Abstract: Si-based anode materials have been widely accepted as one of the most potential candidates for lithium ion batteries due to their abundance and high theoretical specific capacity. However, their practical application is seriously restricted by huge volume change and low intrinsic electric conductivity. Herein, a sandwich structured mesocarbon microbeads/nano-Si/amorphous carbon (MSC) composite was successfully fabricated through simple solution process and magnesiothermic reduction. The MCMB core acts as perfect materials support for nano-Si and conductive network for high electrochemical lithiation stability. Nano-Si provides high lithium storage capacity for enhanced energy density, and the amorphous carbon layer can effectively buffer the volume change from the nano-Si. As a result, the obtained MSC composite with optimal design displays high reversible capacity of 648 mA h g −1 at a current density of 100 mA g −1, along with a satisfactory capacity retention ratio of 90.3% after 100 cycles. To sum up, we develop a simple approach for large-scale preparation of silicon-based composites with high capacity and long-term cycle stability, which shows great potential for applications in the next-generation lithium ion batteries. Graphical abstract: Image 1